Improving the Quality of Slum Settlements to Support Batik Village Tourism in Tanjungbalai City - Jhon Markus Sembiring; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This research aims to research the Improvement of the Quality of Slum Settlements to Support Batik VillageTourism in Tanjungbalai City. The qualitative approach in this study allows for an in-depth analysis of theconditions and efforts to improve the quality of slums around Batik Village, Tanjungbalai City. Through datacollection techniques such as observation, interviews, and documentation, as well as systematic analysistechniques, this study seeks to identify effective measures that can support cultural tourism and empower localcommunities. Research results Overall, improving the quality of slums around Kampung Batik Kota Tanjungbalaihas had a positive impact on tourism development and improving the welfare of the local community. Withinfrastructure support, community participation, and collaboration between the government and the privatesector, Kampung Batik can continue to develop as a unique and attractive cultural tourism destination. Consistentimplementation and continuous monitoring will ensure that environmental quality improvements can continueto support tourism attraction and local economies in the future.